2009
DOI: 10.1186/1756-8722-2-25
|View full text |Cite
|
Sign up to set email alerts
|

The effects of β-glucan on human immune and cancer cells

Abstract: Non-prescriptional use of medicinal herbs among cancer patients is common around the world. The alleged anti-cancer effects of most herbal extracts are mainly based on studies derived from in vitro or in vivo animal experiments. The current information suggests that these herbal extracts exert their biological effect either through cytotoxic or immunomodulatory mechanisms. One of the active compounds responsible for the immune effects of herbal products is in the form of complex polysaccharides known as β-gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
570
2
22

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 748 publications
(600 citation statements)
references
References 69 publications
6
570
2
22
Order By: Relevance
“…These acids retard the growth of carcinoma cell lines and also induce apoptosis (programmed cell death) in carcinoma cells. Though limited data is available, some beneficial effects of β-glucan on carcinoma cells are reported (Murphy et al 2004). Fung Chan et al (2009 reported no direct cytotoxic reports of β-glucan on a panel of common cancer cell lines tested including carcinoma, sarcoma and blastoma.…”
Section: Other Usesmentioning
confidence: 99%
“…These acids retard the growth of carcinoma cell lines and also induce apoptosis (programmed cell death) in carcinoma cells. Though limited data is available, some beneficial effects of β-glucan on carcinoma cells are reported (Murphy et al 2004). Fung Chan et al (2009 reported no direct cytotoxic reports of β-glucan on a panel of common cancer cell lines tested including carcinoma, sarcoma and blastoma.…”
Section: Other Usesmentioning
confidence: 99%
“…Then, the small fragments of β-glucans are released by macrophages and are taken up by circulating granulocytes and monocytes, and dendritic cells. The immune response will then be revealed (Chan et al, 2009;Torello et al, 2012). There is little to no evidence for these hypothesized mechanisms of action in humans.…”
Section: Discussionmentioning
confidence: 99%
“…There is little to no evidence for these hypothesized mechanisms of action in humans. It is also suggested that β-glucans have no direct cytotoxic effects and do not trigger any apoptotic pathways in cancer cells (Chan et al, 2009); however, research has shown that β-glucans augmented antitumor monoclonal antibody-mediated efficacy via stimulation of the innate effector neutrophil complement receptor 3 (Zhong et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] Although there is some evidence to suggest that certain components of the protocol might be beneficial to those with cancer, the evidence is far from conclusive. [24][25][26][27][28][29][30][31] Possible risks associated with the protocol's use can be considered. It is known that in cancer patients, nutritional status interacts with disease factors, treatment factors, and resulting quality of life.…”
Section: Discussionmentioning
confidence: 99%